2022
DOI: 10.29359/bjhpa.14.2.07
|View full text |Cite
|
Sign up to set email alerts
|

External load in male professional volleyball: A systematic review

Abstract: Introduction. The objectives of this systematic review were to identify the volleyball external loads values in the literature and to verify the applicability of different means of quantification and monitoring of these variables during training sessions and matches. Material and methods: This systematic review was produced following the PRISMA statement recommendations, and the search for publications was carried out in the databases PubMed/NCBI, SportDiscus via EBSCOhost, SciELO. 12 studies meet the criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our result showed that the most common jump is the standing jump (performed during block move). Similar to our findings was the study of Pisa et al (2022) where block and attack movements have a higher jump load during matches. Moreover, Piatti et al ( 2022) reported that player type of jumps gives coaches appropriate insight into the physical exertion and technical requirement of each in-game role.…”
Section: Discussionsupporting
confidence: 92%
“…Our result showed that the most common jump is the standing jump (performed during block move). Similar to our findings was the study of Pisa et al (2022) where block and attack movements have a higher jump load during matches. Moreover, Piatti et al ( 2022) reported that player type of jumps gives coaches appropriate insight into the physical exertion and technical requirement of each in-game role.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Sheppard, Gabbett & Stanganelli, (2009) stated that although middle blockers perform more jumps than outside blockers because they have to jump even if they do not meet the ball, it cannot be said that they perform more attacks. Pisa, Zecchin, Gomes & Puggina, (2022) found that middle blockers had a higher jump load, outside blockers made maximum jumps, and setters made medium-height jumps. In block and attack jumps, it was observed that the middle blocker had the highest number of jumps, followed by the opposites.…”
Section: Discussionmentioning
confidence: 96%
“…Although the opposite and the outside hitters frequently perform jumps closer to their maximum height, the middle blockers and the setters are used to greater jumps 11 , 22 , 23 . Indeed, in a 108 training sessions analysis (27 official games and seven friendly matches of elite volleyball team), 6 , 13 observed that the setter performed the highest number of jumps per session (121), followed by the middle blocker (92) and opposite hitter.…”
Section: Discussionmentioning
confidence: 99%
“…The workload in volleyball could be measured as internal and/or external load and could be defined across several parameters, such as volume, frequency, intensity, monotony, and density, among others 7 , 8 . In this respect, while external workload could be described as an indirect measure represented by the amount of the physical work, such as distance, velocity, number of jumps per session, which are the most common measures of external load in different studies 9 11 .…”
Section: Introductionmentioning
confidence: 99%